RETRACTED: Deciphering the Urinary Microbiota Repertoire by Culturomics Reveals Mostly Anaerobic Bacteria From the Gut - Dubourg, Grégory; Morand, Aurélie; Mekhalif, Fatima; Godefroy, Raphael; Corthier, Alice; Yacouba, Abdourahamane; Diakite, Ami; Cornu, Florent; Cresci, Marina; Brahimi, Samy; Caputo, Aurélia; Lechevallier, Eric; et al. (Frontiers in Microbiology, 2020)
Human urine was considered sterile for a long time. However, 423 species have been previously cultured including only 40 anaerobic species. Here, we used culturomics, particularly targeting anaerobes to better understand the urinary microbiota. By testing 435 urine samples, we isolated 459 different bacterial species, including 264 never described in urine, of which 18 were new species. Among the bacterial species identified, 161 were anaerobes (35%). This study increased the known urine repertoire by 39%. Among the 684 bacterial species isolated at least once from urine microbiota, 424 (62%) were previously isolated from gut microbiota, while only 218 (32%) were previously isolated from vagina. In parallel with Lactobacillus, for which passage from the digestive tract to urine or milk has been demonstrated, our results lead to a paradigm shift in the understanding of the urinary microbiota, highlighting that its origin is the gut rather than the vagina.